Revisiting Stakeholder Theory and Environmentalism: Evidence from an Emerging Economy - Saleem, Farida; Zhang-Zhang, Yingying; Malik, Muhammad Imran; Allui, Alawiya (Sustainability, 2020)
In this study, we evaluated corporate environmental activities within the framework of stakeholders’ concerns and taking an emerging economy as the field of study. This paper integrates the stakeholder theory and corporate environmental behavior to develop a model and then tests this model in an emerging economy context. Data were collected through a questionnaire survey from managers operating in a variety of industries in Pakistan. A structural equation modeling technique has been used for data analysis. Results revealed that regulatory bodies are the most significant while media, customers, and activists are insignificant stakeholders. Top management commitment is identified as an important endogenous and exogenous variable.